ANALISIS PENERAPAN GROSS UP METHOD DALAM PERHITUNGAN PAJAK PENGHASILAN PASAL 21 PADA PT PELNAS BINTAN BUGAR BUGAR - Juhli Edi S Simanjuntak; Dwi Susanti (Jurnal Inovasi Penelitian, 2023)
This research was conducted with the aim of knowing how to analyze the application of the Gross Up method and how to calculate income tax article 21 for permanent employees at PT Pelnas Bintan Bugar Bugar. The research approach is a qualitative descriptive study, the type of data used is primary and secondary data, while the collection technique documentation data, observations and interviews, the data analysis technique in this study is a descriptive method, namely the method used to compile, collect, analyze a data collected in the form of numbers.The results of the research conducted at PT Pelnas Bintan Bugar Bugar showed that Article 21 of the gross up income tax method had not been applied to permanent employees in accordance with the applicable tax laws. Obtained corporate income tax that will be paid by PT Pelnas Bintan Bugar Bugar is smaller because there are tax allowances given to employees in accordance with the Article 21 income tax expense that will be paid